The neuroprotective effect of bisperoxovandium (pyridin-2-squaramide) in intracerebral hemorrhage - Liao XY; Lei Y; Chen SF; Cheng J; Zhao D; Zhang ZF; Han X; Zhang Y; Liao HB; Zhuang Y; Chen J; Zhou HB; et al. (Drug Design, Development and Therapy, 2019)
Xin-Yu Liao,1,* Yang Lei,2,* Song-Feng Chen,2 Jing Cheng,3 Dan Zhao,4 Zhi-Feng Zhang,2 Xin Han,5 Ya Zhang,2 Hua-Bao Liao,2 Yang Zhuang,2 Juan Chen,6 Hai-Bing Zhou,5 Qi Wan,7 Ying-Ying Zou,11Department of Pathology and Pathophysiology, Faculty of Basic Medical Sciences, Kunming Medical University, Kunming 650500, People’s Republic of China; 2Department of Physiology, School of Basic Medical Sciences, Wuhan University School of Medicine, Wuhan 430071, People’s Republic of China; 3Department of Neurosurgery, Renmin Hospital of Wuhan University, Wuhan 430060, People’s Republic of China; 4Department of Physiology, School of Basic Medical Sciences, Hubei University of Medicine, Shiyan, Hubei 442000, People’s Republic of China; 5School of Pharmacy, Wuhan University, Wuhan 430071, People’s Republic of China; 6Department of Neurology, The Central Hospital of Wuhan, Tongji Medical College of Huazhong University of Science & Technology, Wuhan 430013, People’s Republic of China; 7Institute of Neuroregeneration & Neurorehabilitation, Collaborative Innovation Center for Brain Science, Department of Neurosurgery of the Affiliated Hospital, Qingdao University, Qingdao 266071, People’s Republic of China*These authors contributed equally to this work Background: The authors have recently designed a new compound bisperoxovandium (pyridin-2-squaramide) [bpV(pis)] and verified that bpV(pis) confers neuroprotection through suppressing PTEN and activating ERK1/2, respectively. Intracerebral hemorrhage (ICH) is the second most common cause of stroke and has severe clinical outcome. In this study, we investigate the effect of bpV(pis) in ICH model both in vivo and in vitro.Materials and methods: The novel drug bpV(pis) was synthesized in the Faculty of Pharmacy, Wuhan University School of Medicine. An ICH model was generated on both SD rats and cells. bpV(pis) was injected into intracerebroventricular or culture media. Western blotting was applied to test the signal pathway. To determine the effect of bpV(pis) on PTEN inhibition and ERK1/2 activation, we measured the phosphorylation level of AKT (a direct downstream target of PTEN that negatively regulates AKT) and ERK1/2. FJC, MTT, and LDH were applied to measure the cell viability. Neurobehavioral tests were performed to measure the effect of bpV(pis).Results: The in vivo results showed that intracerebroventricular administration of bpV(pis) significantly alleviates hematoma, the damage of brain–blood barrier and brain edema. The in vitro results demonstrated that bpV(pis) treatment reduces ICH-induced neuronal injury. Western blotting results identified that bpV(pis) exerts a neuroprotective effect by significantly increasing the phosphorylation level of AKT and ERK1/2 after experimental ICH. Neurobehavioral tests indicate that bpV(pis) promotes functional recovery in ICH animals.Conclusion: This study provides first and direct evidence for a potential role of bpV(pis) in ICH therapy.Keywords: bpV(pis), intracerebral hemorrhage, PTEN, AKT, ERK1/2, neuroprotection